Editorial - Graham Connelly; Sarah Deeley (Scottish Journal of Residential Child Care)
Welcome to the autumn 2024 issue of the Scottish Journal of Residential Child Care (SJRCC). We introduce this issue by saying a big 'thank you' from the editorial team to our readers, at home and, increasingly, internationally. It is clear that being recently listed in the Directory of Open Access Journals (DOAJ) is already bringing our small, Scotland-based journal to a much wider world audience, and, in turn, authors from more countries are entrusting us with their precious research and commentary by submitting articles for review. While on the theme of 'thanks', we also record our appreciation of the members of our international editorial board, and other volunteers, who give their time and expertise to review articles and offer advice to authors.